Detecting Looming Vetoes: Getting the European Parliament’s Consent in Trade Agreements - Peffenköver, Marie (2021)
Since the implementation of the Lisbon Treaty, the European Parliament wields the power of consent over international (trade) agreements, enabling it to threaten a veto. Due to the extensive financial and reputational costs associated with a veto, the European Commission (hereinafter Commission) was expected to read these threats effectively. However, the Commission’s responses to such threats have varied greatly. Building on a fine-grained causal mechanism derived from information processing theory and an extensive process-tracing analysis of seven free trade agreements post-Lisbon, we explain why the Commission has responded differently to looming vetoes. Our analysis reveals that the variation in Commission responses derives from imperfections in its information-processing system, the ‘early-warning system,’ which had to be adapted to the new institutional equilibrium post-Lisbon. Because of this adaption process, factors exogenous to the parliamentary context (‘externalities’) as well as internal uncertainties (‘internalities’) add constant unpredictability to the Commission’s reading of the European Parliament.